(untitled) (Aporte Santiaguino, 2023)
The reduction of formaldehyde, as a common indoor air pollutant, was analyzed using two species of ornamental plants: Sansevieria trifasciata and Spathiphyllum. The study was conducted in an airtight chamber, where formaldehyde was measured every half hour for 22 hours using a formaldehyde meter. The results revealed that the combination of both plants was the most effective, achieving 98% absorption in 22 hours, with 92,5% during the day and 84,5% at night. Spathiphyllum reduced 96% in 22 hours, with 91,5% during the day and 74,75% at night. Meanwhile, Sansevieria trifasciata decreased 75,75% in 22 hours, with 57% during the day and 46,5% at night. These results highlight the importance of plants in improving air quality, with the combination of Sansevieria trifasciata and Spathiphyllum being the most efficient. The variables of light exposure and time of exposure of the plants to formaldehyde also influenced their ability to reduce the pollutant. In conclusion, the potential of using these plant species as an environmentally friendly solution to reduce indoor air pollution and protect population health is demonstrated.